Human keratinocytes adapt to ZnO nanoparticles induced toxicity via complex paracrine crosstalk and Nrf2-proteasomal signal transduction - Wu, Zhuoran (2020)
Zinc oxide nanoparticles (Nano-ZnO) is currently one of the most extensively used inorganic particles in a wide range of skin care and consumable products. Therefore, examining the biological effects of Nano-ZnO, especially in the non-cytotoxic levels, thus holds important contemporary practical implications. Herein, our study demonstrates that long-term conditioning of human keratinocytes (HaCaTs) to non-cytoxic dose of Nano-ZnO (∼100 nm) can induce an adaptive response, leading to an enhancement of the cells tolerance against cytotoxic level of Nano-ZnO. It was found that the Nano-ZnO induced adaptive alteration is mediated by a strong synergism between the generation of reactive oxygen species (ROS) flares by a sub-population of cells that are loaded with Nano-ZnO and upregulation of several pro-inflammatory transcripts. Further studies revealed activation of the nuclear factor (erythroid-derived 2)-like 2 (Nrf-2) stress response pathway and the associated downstream sustained augmented level of chymotrypsin-like 20 s proteasome activity to be the major mechanism underpinning this phenomenon. Interestingly, these cytoprotective responses can further aid the Nano-ZnO conditioned HaCaT cells to cross-adapt to harmful effects of ultraviolet-A (UVA) by reducing radiation-induced DNA damage. Our findings have unveiled a range of previously undocumented potent and exploitable bioeffects of Nano-ZnO induced ROS mediated signaling within the framework of nano-adaptation.